Market segmentation and dimensions of store equity: a study in retail construction - Florêncio, Juliana Cristina Fornabaio; Spers, Eduardo Eugênio; Silva, Hermes Moretti Ribeiro da; Pizzinatto, Nadia Kassouf (Revista de Administração da UFSM, 2020)
This study has its bases on the concept of store equity developed by Hartman and Spiro (2005) and in the empirical model of Teixeira, Oliveira and Pires (2006), which identifies four dimensions: loyalty, memory, quality and image. The objective was to apply and test the dimensions of the model in four distinct retail brands of the building and construction segment of São Paulo, compare their store equity and segment the consumers. In each store (160 total), forty interviews were conducted. By exploratory factor analysis, it was possible to observe five dimensions related to the store equity construct: loyalty, store image, customer satisfaction, and customer care and service conformity. Through cluster analysis, respondents were classified into three different groups of consumers according to the five dimensions identified and received the categories of Unprepared, Demanding and Accustomed. Theoretical and managerial implications reinforce the possibility of applying the store equity as a customer segmentation variable in the construction retail segment.